The effects of promotion program for HIV prevention behaviors of grade 8 students in Bangkok - ภิยโยทัย สิริพร; ธีระวิวัฒน์ มณีรัตน์; อิมามี นิรัตน์ (Disease Control Journal, 2018)
At present, HIV infection in Thai youth is increasing due to harmful risk behaviors. This quasi-experimental research aimed to study the effect of a program promoting HIV prevention behaviors among junior high school students. The studied samples were 24 grade 8th students in a school in Bangkok. One grade-8 classroom was randomly selected from the Bangkok educational region; and all students of the class were recruited for the study. The study was conducted in three phases. The first phase emphasized on the study of primary data (elicit knowledge and perception) regarding AIDS and HIV prevention of the youth for developing the study program. The second phase dealed with implementation of the program learning activities. The third phase involved evaluation of the program effectiveness. Data were collected by a self-administered questionnaire and were described by frequency, percent, mean, standard deviation and paired t-test. Results of the study revealed that after the experimental group participated in the program, they gained significantly higher mean scores on knowledge about AIDS and HIV prevention, attitude toward HIV prevention behaviors, and perceived self-efficacy in prevention of HIV (p<0.05) when compared to those before participating in the program. The mean score of HIV prevention behaviors was found to be higher than that gained before the experimentation, though it was not statistically significant (p>0.05). These results indicated the effectiveness of the program which was developed and based on the elicit knowledge and perceptions of the youth. Therefore, the program could be applied to design learning activities for students in other junior high schools as well as other related age group students in order to enhance the students to gain more knowledge and skills in performing proper HIV prevention behaviors.